Intensive and extensive rice farm adaptations in salinity-prone areas of the Mekong Delta - Bradford Mills; Dung Phuong Le; Duong Phuc Ta; Lien Nhu; Danh Thanh Vo; Ricardo Labarta (Climate and Development, 2023)

DNA fingerprinting reveals varietal composition of Vietnamese cassava germplasm (Manihot esculenta Crantz) from farmers’ field and genebank collections - John Ocampo; Tatiana Ovalle; Ricardo Labarta; Dung Phuong Le; Stefan de Haan; Nguyen Anh Vu; Le Quy Kha; Luis A. Becerra Lopez-Lavalle (Plant Molecular Biology, 2022)
Key message A molecular analysis using informative SNP markers in 1570 clones of cassava from Vietnam reveals varietal composition from farmers’ field and genebank collections Abstract Cassava is the most important smallholder cash crops in Southeast Asia and is especially used in industrial products. Yet, systematic genetic studies on molecular markers from Vietnamese germplasm have not been considered for breeding and conservation programs. We conducted a molecular analysis of 1570 clones of cassava germplasm from farms across six agro-ecological zones using informative SNP markers. We unraveled the genetic diversity and population structure and provided insights into the value of breeding and conservation programs. Duplicated genotypes comprised 98% of the total sample of the Central Highlands region. Ninety-six SNPs were amplified Central Highlands and South East provinces had the highest allelic richness, covering up to 83% of alleles. The average observed heterozygosity ( Ho = 0.43) was slightly higher than expected ( He = 0.40) across SNP markers, suggesting an excess of heterozygotes plants. Diversity indexes indicated that cassava populations from North West and Eastern Vietnam are genetically diverse (mean He = 0.40). Genetic parentage tests identified 85 unique genetic groups within the varieties KM94, KM419, BRA1305, KM101, KM140, PER262, KM60, KM57 and two unidentified varieties, which accounted for 82% of the frequency distribution. KM94 is the most dominant variety in Vietnamese farms surveyed (38%), reflecting its superior quality and productivity. Discriminant analysis of principal components (DAPC) revealed four main subgroups, which were partially corroborated by neighbor joining (NJ) analyses. After removing duplicates, 31 unique genotypes were distributed across five of the agro-ecological zones. These were well distributed in the subgroups revealed via DAPC and NJ analyses. The genetic groups identified herein could be used to select unique accessions that should ideally conform with ex situ germplasm collections and identify areas where on-farm conservation programs should be targeted. Newly identified genotypes may also contribute as genetic breeding resources that could be used to adapt cassava to future changes and farmers’ needs.

The contribution of the CIAT genebank to the development of iron-biofortified bean varieties and well-being of farm households in Rwanda - Stefania Sellitti; Kate Vaiknoras; Melinda Smale; Nelissa Jamora; Robert Andrade; Peter Wenzl; Ricardo Labarta (Food Security, 2020)

Changes in food access by mestizo communities associated with deforestation and agrobiodiversity loss in Ucayali, Peruvian Amazon - Genowefa Blundo-Canto; Gisella S. Cruz-Garcia; Elise F. Talsma; Wendy Francesconi; Ricardo Labarta; Jose Sanchez-Choy; Lisset Perez-Marulanda; Paula Paz-Garcia; Marcela Quintero (Food Security, 2020)
Few longitudinal studies link agricultural biodiversity, land use and food access in rural landscapes. In this paper, we test the hypothesis that, in a context of economic change, cash crop expansion is associated with deforestation, reduced agrobiodiversity and changes in food access. For this purpose, we analysed data collected from the same 53 upland and floodplain mestizo households in Ucayali, Peru, in 2000 and 2015. We found an emerging transition towards less diversified food access coupled with loss of forest cover and reduced agricultural biodiversity. In 2015, diets appeared to rely on fewer food groups, fewer food items, and on products increasingly purchased in the market compared to 2000. Wild fruits and plants were mentioned, but rarely consumed. Agricultural production systems became more specialised with a shift towards commercial crops. Peak deforestation years in the 15-year period appeared linked with incentives for agricultural expansion. Our results suggest an overall trend from diversified productive and “extractive” systems and more diverse food access, towards specialized productive systems, with less diverse food access and stronger market orientation (both in production and consumption). The assumption in the food and agricultural sciences that increased income and market-orientation is linked to improved food security, is challenged by our integrated analyses of food access, agrobiodiversity, land use and forest cover. Our results highlight the importance of longitudinal, multidimensional, systemic analyses, with major implications for land use, food and health policies. The potential risks of parallel homogenisation of diets and agricultural production systems require interdisciplinary research and policies that promote integrated landscape approaches for sustainable and inclusive food systems.

Benchmarking Food Crop Markets in Southern Africa: The Case of Potatoes and Potato Products 1961–2010 - Gregory J. Scott; Ricardo Labarta; Víctor Suarez (American Journal of Potato Research, 2013)

Booms, Busts, and Emerging Markets for Potatoes in East and Central Africa 1961–2010 - Gregory J. Scott; Ricardo Labarta; Víctor Suarez (Potato Research, 2013)